2014
DOI: 10.1155/2014/976428
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Impairs p53 Activity in HepG2 Cells

Abstract: Cadmium and cadmium compounds are contaminants of the environment, food, and drinking water and are important constituents of cigarette smoke. Cd exposure has also been associated with airborne particulate CdO and with Cd-containing quantum dots in medical therapy. Adverse cadmium effects reported in the literature have stimulated during recent years an ongoing discussion to better elucidate cadmium outcomes at cell and molecular level. The present work is designed to gain an insight into the mechanism of p53 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 35 publications
(54 reference statements)
1
17
0
1
Order By: Relevance
“…Exposure to Cd leads to the transformation of prostate epithelial cells and a significant upregulation of KRAS (>20-fold) as well as the downregulation of 12 miRNAs, with miR-373 exhibiting the largest (11-fold) downregulation, and only a slight (6-fold) increase in miR-9 [68]. Cd exposure also can upregulate miR-372, which affects p21Cip1/WAF-1 expression in hepatic cell lines [69]. Changes in p21 activity will in turn alter p53 activity.…”
Section: Cadmium-associated Changes In Mirna Expressionmentioning
confidence: 99%
“…Exposure to Cd leads to the transformation of prostate epithelial cells and a significant upregulation of KRAS (>20-fold) as well as the downregulation of 12 miRNAs, with miR-373 exhibiting the largest (11-fold) downregulation, and only a slight (6-fold) increase in miR-9 [68]. Cd exposure also can upregulate miR-372, which affects p21Cip1/WAF-1 expression in hepatic cell lines [69]. Changes in p21 activity will in turn alter p53 activity.…”
Section: Cadmium-associated Changes In Mirna Expressionmentioning
confidence: 99%
“…22,23 Also, exposure to Cd in pregnant women has been associated with functional loss and compromised p53-mediated DNA damage repair resulting to increased risk of preeclampsia. 24,25…”
Section: Cadmium As Antimetabolite To Zincmentioning
confidence: 99%
“…This may result in genome instability and cancer occurrence (Spike and Wahl, 2011). It was showed that cadmium can have effect on the both structure and function of p53 through different mechanisms such as apoptosis (Ho, 2004;Urani et al, 2014). Cadmium can bind to thiol groups as well as substitute with zinc in structure of P53.…”
Section: Cadmium Genotoxicity and The Influence On P53 Proteinmentioning
confidence: 99%